-18=-3(-6+n)

Simple and best practice solution for -18=-3(-6+n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=-3(-6+n) equation:



-18=-3(-6+n)
We move all terms to the left:
-18-(-3(-6+n))=0
We add all the numbers together, and all the variables
-(-3(n-6))-18=0
We calculate terms in parentheses: -(-3(n-6)), so:
-3(n-6)
We multiply parentheses
-3n+18
Back to the equation:
-(-3n+18)
We get rid of parentheses
3n-18-18=0
We add all the numbers together, and all the variables
3n-36=0
We move all terms containing n to the left, all other terms to the right
3n=36
n=36/3
n=12

See similar equations:

| 2x+3-8x+1=2x-8x+6 | | –2x=–14 | | 4x^2-16x-356=0 | | 5x+18+3x-2-4x=2x+24 | | (x-5)(x-2)(x+3)=0 | | 10(-10+n)=-180 | | 6-12x+15=7 | | -7+m/9=-6 | | 8-4p=72 | | |n+8|=15 | | -3b+7b=-20.5 | | F(x)=-16x+8 | | 2^x-3=8^4x | | 21+3=35y | | 365x=1000x | | 10x-8=8x-8 | | 16*p=208 | | 71=10n+1 | | x^2+27.9x+217.9=0 | | 3x-2=6=x | | 8^3x-2=2^2x+7 | | 4-3=-6h | | 2c(4c+3)^2=0 | | (2x+22)=(6x+6) | | 9x–4+4x=+5x+19 | | 11y+15=81 | | V^2-56x=0 | | 6x=6x+0,5 | | 0=x^-15x+36 | | 4x+1-x=10 | | -3+7x-5-3x=8 | | 4x-11=2x+8 |

Equations solver categories